Mindfulness of Career Counselors within the Omani's Context - Bakkar S. Bakkar; Muna A. Al-Bahrani (Sultan Qaboos University, 2015)
This study aimed to explore the variation of Omani career counselors' mindfulness level, in relation to their gender, qualifications, experience, age, and social status. The Mindful Attention Awareness Scale was used to assess the mindfulness level of 164 career counselors from the Sultanate of Oman. The findings showed that mindfulness level was high among career counselors. The results also revealed significant differences due to gender. Males' level of mindfulness was higher than females. N o differences were found due to qualifications, experience, age, and social status on the level of mindfulness. Recommendations suggested further research to examine the relationship between mindfulness in career counselors and positive client outcomes.